An Event “Like a Movie”? Hollywood and 9/11 - Rickli, Christina (Current Objectives of Postgraduate American Studies, 2012)
Footage of the terrorist attacks of September 11, 2001 provoked a wide spectrum of viewers to state that what they were witnessing was “like a movie.“ In a first part, this essay discusses the salience of such a simile by comparing the aesthetics and content of 9/11-footage to the one of Hollywood disaster films. In a second part, Hollywood’s immediate reactions as well as its recent movie representations of 9/11 are analyzed.